Os segredos visíveis da cidade: a efemeridade da luz e da sombra na linguagem fotográfica - COLLANTES, Galo Raúl Yépez (2010)
The present work proposes a theoretical reflection around the photographic images produced by the author between the years 2001 and 2006 during the passing of certain visual effects of a transitory nature that appear in the city. The analysis of images is proceeded by a historical review on urban morphology and iconography; the image of the city; and on a selection of American and European photographers that included the city within their preferred subject matter. In the second part of the article the intention is to be explicit on some of the positions that underlie the fundamental concepts of the author's work, starting with the explanation of the language around the ephemeral and then developing aspects relating to the technical image, an unbreakable element of the photograph. Finally, the study focuses on an interpretative and descriptive analysis, looking at historical, technical, aesthetic and conceptual elements of the most representative images that form part of the author's three thematic exhibitions. At this stage it explores: the embedding in photographic aesthetics of facets of simple and routine urban daily life; the potential of reflection in water on the ground; as well as the dominance of shadows in the contemporary vision of creative photography.